Vegetative dormancy of pecan - A review - Crosa, Claudia Farela Ribeiro (2021)
Pecan is a fruit tree that needs low temperatures in the winter, so that it can induce and overcome dormancy and reestablish a new cycle of productive development. Through this review, the producer will be able to have reliable information on the climatic requirement of the crop, in order to support his decision making on management practices that reduce the damage caused by these phenomena and serve to optimize the production system, improving his profits. In view of this, it becomes propitious to provide information about the crop with a focus on the cold demand required to overcome the dormancy of pecan cultivars. It was possible to verify the divergence between the authors in relation to the need for cold for pecan and the need for more tests about the products used to induce sprouting in pecan.